The influence of different Cardan sequences on three-dimensional cycling kinematics - Sinclair, J.; Hebron, J.; Hurst, H.; Taylor, P. (Human Movement, 2013)
Three-dimensional (3-D) kinematics are widely utilized to quantify movement in cycling analyses. Three-dimensional angular kinematics are obtained using the Euler/Cardan technique, however, Cardan angles are influenced by their ordered sequence and may affect the resultant angular parameters. An XYZ sequence of rotations is currently recommended, although this technique may not always be appropriate when coronal and transverse plane angles are quantified. This study aimed to determine the influence of the six available Cardan sequences on 3-D lower extremity kinematics during cycling. Methods. Kinematic information was obtained from twelve cyclists using an optoelectronic 3-D motion capture system operating at 250 Hz. Repeated measures ANOVAs were used to compare the kinematic parameters obtained using the six Cardan sequences, and intraclass correlations were employed to detect the presence of crosstalk across planes. Results. The results show that discrete kinematic parameters in the sagittal, coronal and transverse planes were significantly greater when using the YXZ and ZXY sequences. It was also observed that these sequences were associated with the strongest correlations from the sagittal plane and also exhibited evidence of gimbal lock. Conclusions. The results suggest that the accurate representation of 3-D kinematics during cycling should continue utilizing the XYZ sequence and avoid the use of the YXZ and ZXY sequences.